Penerapan Model Teams Games Tournament Berbantuan Media Pemprof untuk Meningkatkan Hasil Belajar Siswa Kelas IV Sekolah Dasar - Prisma Adi Putra; Erik Aditia Ismaya; Muhammad Noor Ahsin (Jurnal Prasasti Ilmu, 2021)
The purpose of this study is to analyze the improvement of teacher skills and increase learning outcomes of students in class IV SD 5 Lau in learning Theme 4 by applying the learning model Team Games Tournament assisted by the Pemprof media. The research method used is classroom action research (CAR) carried out in two cycles, each cycle consisting of four stages namely planning, implementation, observation and reflection. The research location is SD 5 Lau which is located at Lau Village RT 05 / RW 05 Dawe District, Kudus Regency. The subjects of the study were the fourth grade students of SD 5 Lau in the first semester of the 2019/2020 school year, totaling 16 students, consisting of eight male students and eight female students. Research data sources are teachers and students. Data collection techniques include interview, observation, test and documentation techniques. The validity of the data used is Expert Judgment using qualitative and quantitative data analysis techniques.  The results showed an increase in teacher teaching skills as well as student learning outcomes in the realm of knowledge and the realm of skills. The teaching skills of teachers in the first cycle obtained a percentage of 76% and in the second cycle increased to 85.50% Student learning outcomes in the realm of social science content in the first cycle obtained an average of 76.25 with 75% classical completeness and Indonesian content with an average 73.12 with classical completeness 56.25%. In the second cycle the IPS load increased for an average of 77.5 with a classical completeness of 81.25% and an Indonesian content with an average of 84.06 with a classical completeness of 81.25%. Student learning outcomes in the realm of cycle I gained a percentage of 70.57%, increasing in cycle II to 80.08%.